Strengthening of capacities to improve the processes of contracting and acquisitions of the state in the "Huampaní Resort", 2014 - Sánchez Chero, José Antonio (2017)
The Vacation Center Huampaní through managing logistics area goods and services required for all user areas, but there are administrative and operational deficiencies of the employees that make up the contracting and procurement processes Vacation Center Huampaní, 2014. The issue is What effect does implementing a capacity building program to enhance job performance of the employees participating in the process of procurements "Vacation Center Huampaní" Year 2014? The specific objectives are: The determination of the level of technical knowledge by applying the survey pretest. The design capacity building program to improve the processes of procurements Huampaní Vacation Center. Implementation of the program to the experimental group according to institutional needs. Program evaluation is then determined by applying the survey Post Test and finally the results obtained from surveys Pre test and post test to compare the initial research. The methodology is quantitative experimental design applied to a population sample of 58 employees and technique of data collection is the survey, analysis and data interpretation concludes improving 71 % the administrative activities of the employees participating in the process of procurements Huampaní Vacation Center , 2014.